Training Chemistry Teachers' Understanding in Creating Learning Evaluation Media Using the Wordwall Application - Rilia Iriani; Leny Leny; Misi Jini Rinaya; Misbah Misbah; Andy Azhari; Nana Nana; Nika Sopranti; Muhaimin Muhaimin; Hakki Norhasanah (Universitas Lambung Mangkurat, 2024)
This community service activity aims to assist chemistry teachers in the Banjar Regency Chemistry Teachers Working Group (MGMP) in developing learning evaluation materials. This training aims to improve the quality of learning in the Independent Curriculum for chemistry teachers in creating learning evaluations using Wordwall. Based on the questionnaire results filled out by MGMP chemistry teachers in the Banjar Regency, it was found that 50% of teachers stated that they were skilled enough in using technology in preparing learning evaluation materials. The methods in this activity are divided into three stages: pre-implementation, implementation, and post-implementation. Considering this condition, the community service team needs to address the problems teachers face by conducting training on preparing IT-based teaching materials held at SMAN 1 Martapura with two offline meetings attended by 21 teachers. Based on the training results, there was an improvement in teachers' understanding of creating interactive evaluation materials using Wordwall, and teachers' responses to the activity showed a good category. The interactive evaluation products produced can be used to assist the chemistry learning process.